INDEED–Utilization and Cross-Sectoral Patterns of Care for Patients Admitted to Emergency Departments in Germany: Rationale and Study Design - Fischer-Rosinský, Antje; Slagman, Anna; King, Ryan; Reinhold, Thomas; Schenk, Liane; Greiner, Felix; von Stillfried, Dominik; Zimmermann, Grit; Lüpkes, Christian; Günster, Christian; Baier, Natalie; Henschke, Cornelia; et al. (Frontiers in Public Health, 2021)
Introduction: The crowding of emergency departments (ED) has been a growing problem for years, putting the care of critically ill patients increasingly at risk. The INDEED project’s overall aim is to get a better understanding of ED utilization and to evaluate corresponding primary health care use patterns before and after an ED visit while driving forward processes and methods of cross-sectoral data merging. We aim to identify adequate utilization of EDs and potentially avoidable patient contacts as well as subgroups and clusters of patients with similar care profiles. Methods: INDEED is a joint endeavor bringing together research institutions and hospitals with EDs in Germany. It is headed by the Charité - Universitätsmedizin Berlin, collaborating with Otto von Guericke University Magdeburg, Technische Universität Berlin, the Central Research Institute of Ambulatory/Outpatient Health Care in Germany (Zi), and the AOK Research Institute as part of the Federal Association of AOK, as well as experts in the technological, legal, and regulatory aspects of medical research (TMF). The Institute for Information Technology (OFFIS) was involved as the trusted third party of the project. INDEED is a retrospective study of approximately 400,000 adult patients with statutory health insurance who visited the ED of one of 16 participating hospitals in 2016. The routine hospital data contain information about treatment in the ED and, if applicable, about the subsequent hospital stay. After merging the patients’ hospital data from 2016 with their outpatient billing data from two years before to one year after the ED visit (years 2014-2017), a harmonized dataset will be generated for data analyses. Due to the complex data protection challenges involved, first results will be available in 2021. Discussion: INDEED will provide knowledge on extracting and harmonizing large scale data from varying routine ED and hospital information systems in Germany. Merging these data with the corresponding outpatient care data of patients offers the opportunity to characterize the patient's treatment in outpatient care before and after ED use. With this knowledge, appropriate interventions may be developed to ensure adequate patient care and to avoid adverse events such as ED crowding.